2000
DOI: 10.1089/thy.2000.10.779
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy Considerations When Using Early (Four- or Six-Hour) Radioactive Iodine Uptake to Predict Twenty-Four-Hour Values for Radioactive Iodine Dosage in the Treatment of Graves' Disease

Abstract: Although literature has offered methods to predict 24-hour radioactive iodine uptake values from early (4- to 6-hour) measurements, the resultant dosage errors have not been examined. Potential errors include underdosage, overdosage, and a failure to recognize rapid turnover patients (early-to-late uptake ratios > or = 1) who are at high risk for treatment failure and full-body radiation exposure. We developed and tested a novel method for minimizing error involved in using a single early uptake measurement to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…All other factors, including gender (P = 0.266), age (P = 0.452), thyroid volume (P = 0.291), TSH (P = 0.497), FT4 (P = 0.096), Cre (P = 0.282), TRAb2 (P discussion Table 3 compares the present early-to-late RAIU conversion equation and several other early-to-late RAIU conversion equations that have been previously reported by other investigators [1,3,4]. These previously reported equations suggest a stronger correlation between early RAIU and late RAIU than the present equation, which employs only 3-hour RAIU.…”
Section: Measurementssupporting
confidence: 55%
See 3 more Smart Citations
“…All other factors, including gender (P = 0.266), age (P = 0.452), thyroid volume (P = 0.291), TSH (P = 0.497), FT4 (P = 0.096), Cre (P = 0.282), TRAb2 (P discussion Table 3 compares the present early-to-late RAIU conversion equation and several other early-to-late RAIU conversion equations that have been previously reported by other investigators [1,3,4]. These previously reported equations suggest a stronger correlation between early RAIU and late RAIU than the present equation, which employs only 3-hour RAIU.…”
Section: Measurementssupporting
confidence: 55%
“…In the present study, none of the patients with Graves' disease had rapid turnover. Morris et al [4] also reported that Graves' disease patients with 4-hour RAIU values of 77% or greater also should obtain 24-hour RAIU values, probably due to rapid turnover. However, only 7 of 66 patients had 3-hour RAIU values greater than 77% in the present study, and none of those 7 patients had rapid turnover.…”
Section: Measurementsmentioning
confidence: 98%
See 2 more Smart Citations
“…Although RAIU is the most reliable method to differentiate GD from PT (11)(12)(13)(14), it is contraindicated when patients are lactating, and not all clinics are well equipped to perform RAIU. Therefore, a number of studies have been undertaken to search for simple and practical parameters that might allow differentiation between the two entities.…”
Section: Introductionmentioning
confidence: 99%